A Multivariate Analysis of Human Capital: Evidence from Readymade Garments Industry of Bangladesh - Kamal , Md. Aktar; Begum, Noor Nahar (Asian Journal of Empirical Research, 2019)
The aim of the research is to find the association between human capital and financial and non-financial performance. A self-administered survey instrument is developed consisting 26 items under three parts. Both primary and secondary data have been used in this study. In order to collect primary data, face-to-face interview method was used. The result provides evidence that human capital is significantly associated with financial and non-financial performance of an organization. That means skills, education and training, knowledge and competencies, and positive attitudes are vital elements to increases organizational performance. The study recommended the BGMEA, BKMEA, entrepreneurs, policy makers, and investors to concentration on fundamental variables that are influencing the development of human capital in RMG industry of Bangladesh.